Journal of Drug Policy Analysis : A Journal of Substance Abuse Control Policy (De Gruyter, 2008)
Journal of Drug Policy Analysis publishes peer-reviewed articles related to every aspect of the problems posed by abusable psychoactives, licit and illicit, anywhere in the world. We publish analytic contributions to the public and scholarly conversation about how to deal with the issues surrounding drug policy.